2000
DOI: 10.1111/j.1348-0421.2000.tb02488.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Serological Properties of Lipopolysaccharides from Vibrio parahaemolyticus O‐Untypeable Strains Isolated from Patients

Abstract: Chemical and serological studies have been carried out on the O-antigenic lipopolysaccharides (LPS) of six strains, U-6443, W-90144, X-3972, AD-7999, 90A-6611 and KX-V212, of Vibrio parahaemolyticus isolated from patients. The O-serotypes of these strains have not been identified because they were not agglutinated by any diagnostic antisera against known O-serotype strains. A compositional sugar analysis of their LPS revealed that out of the six O-untypeable (OUT) strains, U-6443, W-90144 and AD-7999 strains b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…, 1995). The reason for this discrepancy may arise from the fact that the O‐serotypes of many strains have not been identified because they are not agglutinated by diagnostic antisera against known O‐serotype strains (Hashii et al. , 2000), and many strains remain untypeable (Kaysner & DePaola, 2004).…”
Section: Typing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…, 1995). The reason for this discrepancy may arise from the fact that the O‐serotypes of many strains have not been identified because they are not agglutinated by diagnostic antisera against known O‐serotype strains (Hashii et al. , 2000), and many strains remain untypeable (Kaysner & DePaola, 2004).…”
Section: Typing Methodsmentioning
confidence: 99%
“…, 2000), and many strains remain untypeable (Kaysner & DePaola, 2004). Compositional sugar analysis was evaluated by Hashii et al. (2000) to characterise the lipopolysaccharide of six untypeable (OUT) strains, and the study found that the O‐serotype of two of the OUT strains employed was not a previously known O‐serotype and represented a new serotype that had not been earlier reported.…”
Section: Typing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…parahaemolyticus serotyping, but frequently V. parahaemolyticus strains are not agglutinated by any diagnostic antisera against known serotypes and are, therefore, not typable [3, 5–7]. For several pathogenic bacterial species, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Many V. parahaemolyticus serotypes have been identified as pandemic clones, and certain serotypes, for example O3:K6, O1:KUT and O4:K68, are generally considered to be more virulent than others (Jones et al 2012; Nair et al 2007). Agglutination tests are the gold standard for V. parahaemolyticus serotyping but frequently, V. parahaemolyticus strains are non-typable with agglutination tests in routine screening (Gavilan, Zamudio, and Martinez-Urtaza 2013; Gil et al 2007; Hashii et al 2000; Jones et al 2012). For several pathogenic bacterial species, e.g.…”
Section: Introductionmentioning
confidence: 99%